68th Open Seminar on Acoustics September 12 – 16, 2022, Solina, Poland - Seminar on Acoustics, 68th Open (Archives of Acoustics, 2022)
Open Seminar on Acoustic is an annual conference that brings together researchers and scientists from acoustics. It is organized under the patronage of the Committee on Acoustics of the Polish Academy of Sciences in turns by different divisions of Polish Acoustical Society – in 2022 by the Rzeszów Division of Polish Acoustical Society jointly with the College of Natural Sciences, University of Rzeszów. It is our pleasure to present abstracts of the papers submitted for the 68th Open Seminar on Acoustics – OSA 2022 – that was held September 12–16, 2022 in the Solina Resort located in the South-East Poland.